2017
DOI: 10.1038/srep39498
|View full text |Cite
|
Sign up to set email alerts
|

Local alignment vectors reveal cancer cell-induced ECM fiber remodeling dynamics

Abstract: Invasive cancer cells interact with the surrounding extracellular matrix (ECM), remodeling ECM fiber network structure by condensing, degrading, and aligning these fibers. We developed a novel local alignment vector analysis method to quantitatively measure collagen fiber alignment as a vector field using Circular Statistics. This method was applied to human non-small cell lung carcinoma (NSCLC) cell lines, embedded as spheroids in a collagen gel. Collagen remodeling was monitored using second harmonic generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…Our quantification of ECM remodeling showed that collagen fiber alignment was higher in Matrigel-containing hydrogels (CM and CM+) compared to collagen only hydrogels (C), indicating that hydrogel composition and stiffness are crucial determinants of the extent of matrix remodeling. Indeed, H1299 cells were able to align the collagen fibers in all three hydrogels, a phenomenon that has been associated with malignancy and cell invasiveness [40]. These results are similar to previous studies reported for different types of cancer including glioblastoma (U87 tumor spheroids) [41] and breast cancer (tumors in vivo) [42].…”
Section: Discussionsupporting
confidence: 88%
“…Our quantification of ECM remodeling showed that collagen fiber alignment was higher in Matrigel-containing hydrogels (CM and CM+) compared to collagen only hydrogels (C), indicating that hydrogel composition and stiffness are crucial determinants of the extent of matrix remodeling. Indeed, H1299 cells were able to align the collagen fibers in all three hydrogels, a phenomenon that has been associated with malignancy and cell invasiveness [40]. These results are similar to previous studies reported for different types of cancer including glioblastoma (U87 tumor spheroids) [41] and breast cancer (tumors in vivo) [42].…”
Section: Discussionsupporting
confidence: 88%
“…The motivation for this extension is that tumor spheroids are able to replicate the main structural and functional properties of solid tumors 10 , including the individual and collective invasion into the surrounding matrix 11 . In particular, it has been hypothesized that the collective traction force of a whole tumor may alter the mechanics of the extracellular matrix and facilitate invasion by aligning collagen fibers radially away from the tumor [12][13][14] . However, current 3D finite element force reconstruction methods for single cells, especially in a non-linear material such as collagen, are computationally too slow for analyzing large (∌0.5 mm) tumor spheroids.…”
Section: Mainmentioning
confidence: 99%
“…In this work, we did not specifically consider many other microenvironmental players such as signaling networks [131], human neutrophil elastase as a therapeutic target in the absence [132, 133] and presence [134] of LPS, endogenous NK immune dynamics [40, 135], angiogenesis from blood vessels [136–138], ECM remodeling [139], or growth factors such as epidermal growth factor (EGF) [140, 141], and CSF-1 [7, 142]. These factors may play critical roles in cancer progression.…”
Section: Discussionmentioning
confidence: 99%